Diversity management in the Context of Corporate Social Responsibility - Bednaříková, Marie; Košťálová, Jana; Vávra, Jan; Halamová, Denisa (VGTU Publishing House Technika, 2018)
During last years there are many new modern attitudes and trends in the field of human resources man-agement. The article is focused to one of these trends – diversity management. The aim of the authors is to evaluate single components of diversity management namely in the context of corporate social responsibility (CSR). In addition different possibilities of application of diversity management in practice as instruments of CSR are submitted to analysis. The end of this article shows the results of research oriented to experience with diversity management put into practice in the selected companies in the Czech Republic.
Diversity management v kontextu Společenské odpovědnosti firem
Keywords: Diversity management; corporate social responsibility; human resources management; application of diversity management in practice; application of diversity management in Czech firms.; Diversity management; společenská odpovědnost firem; řízení lidských zdrojů; aplikace diversity managementu v praxi; aplikace diversity managementu v českých firmách.